2016
DOI: 10.1039/c6cp00458j
|View full text |Cite
|
Sign up to set email alerts
|

A graphene-coupled Bi2WO6 nanocomposite with enhanced photocatalytic performance: a first-principles study

Abstract: An experimentally synthesized graphene/Bi2WO6 composite showed an enhancement of the visible-light photocatalytic activity, while the underlying mechanism is not known. Here, first-principles calculations based on density functional theory were performed to explore the various properties of the graphene/Bi2WO6(010) composite aiming at gaining insights into the mechanism of its photocatalytic activity. The stability, electronic properties, charge transfer, and visible-light response were investigated in detail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…4 ), and E(BiVO 4 ) are the total energies of the relaxed BiVO 4 /g-C 3 N 4 heterostructure, g-C 3 N 4 (001), and BiVO 4 (010) slabs, respectively; S is the area of the interface. The calculated adhesion energies for BiVO 4 /SL-g-C 3 N 4 , BiVO 4 /BL-g-C 3 N 4 , and BiVO 4 /TL-g-C 3 N 4 heterostructures are -0.20 eV/Å 2 , -0.25 eV/Å 2 , and -0.18 eV/Å 2 , respectively, suggesting that these structures are stable.These adhesion energies are consistent with those for g-C 3 N 4 (001) on the Zn 2 GeO 4 (110) surface (-0.18 eV/Å 2 )[61] and graphene-coupled Bi 2 WO 6 (010) surface (-0.18 eV/Å 2 )[8]. It should be noted that the calculated adhesion energy is significantly greater than that for typical vdW systems such as graphite, suggesting that both physical and chemical effects contribute to the surface adhesion.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…4 ), and E(BiVO 4 ) are the total energies of the relaxed BiVO 4 /g-C 3 N 4 heterostructure, g-C 3 N 4 (001), and BiVO 4 (010) slabs, respectively; S is the area of the interface. The calculated adhesion energies for BiVO 4 /SL-g-C 3 N 4 , BiVO 4 /BL-g-C 3 N 4 , and BiVO 4 /TL-g-C 3 N 4 heterostructures are -0.20 eV/Å 2 , -0.25 eV/Å 2 , and -0.18 eV/Å 2 , respectively, suggesting that these structures are stable.These adhesion energies are consistent with those for g-C 3 N 4 (001) on the Zn 2 GeO 4 (110) surface (-0.18 eV/Å 2 )[61] and graphene-coupled Bi 2 WO 6 (010) surface (-0.18 eV/Å 2 )[8]. It should be noted that the calculated adhesion energy is significantly greater than that for typical vdW systems such as graphite, suggesting that both physical and chemical effects contribute to the surface adhesion.…”
supporting
confidence: 84%
“…One of the most widely explored strategies is the use of photocatalytic heterojunctions [2,[5][6][7]. Previous work [8,9] has demonstrated that the construction of two semiconductors with suitable electronic structures may exhibit superior photoactivity than single photocatalysts. In particular, a type II band alignment at the heterostructure interface can facilitate rapid separation of photogenerated electron−hole pairs, resulting in significantly improved photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of Bi-O termination was also suggested in a previous computational study. 60 Furthermore, monolayer Bi 2 WO 6 was recently synthesized and suggested to exhibit Bi-O termination. 23…”
Section: Surfaces and Band Energiesmentioning
confidence: 99%
“…The enhanced charge transfer and visible light absorption of graphene/anatase TiO 2 (G/ATN) and graphene/Bi 2 WO 6 (010) nanocomposites was attributed to the difference in their work functions within first‐principles DFT calculation. The Bader charge and charge distribution analysis revealed a strong covalent bonding between graphene and monolayer Bi 2 WO 6 (010) surface, which induces a narrow band gap.…”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%